Perceived Income Justice Depends on the Economy - Stefan Liebig; Peter Valet; Jürgen Schupp (Weekly Report, 2010)
At least half of all employees in Germany described their wages in all three survey years under consideration here - 2005, 2007, and 2009 - as just. Still, major changes occurred over this period in how people perceived their earnings. Data from the Socio- Economic Panel (SOEP) Study show that after an increase in income dissatisfaction in 2007, the percentage of the population who consider their income unjust has again decreased substantially in 2009 - at 30 percent - to 2005 levels. This suggests that in times of economic crisis, people are willing to lower their earnings expectations, while in times of economic growth - like the year 2007 - they expect to share in the benefits of increased prosperity. The analysis shows that it was mainly people in the low to medium income range and in particular skilled workers who perceived their net income as unjust, a perception that remained stable over time. This is partly due to the income taxes paid by these groups. In the upper income segment, in contrast, no negative effect of the income tax burden on perceived income justice is found. Finally, the results confirm previous studies indicating that even in a world in which everyone received the wages they subjectively perceived to be fair, income differences between men and women would still persist. Women's income expectations are significantly lower than men's - even within the individual occupational groups.
Keywords: D31; D63; 330; Justice; SOEP; Inequality